Flipped Classroom sebagai Alternatif Pembelajaran pada Mata Pelajaran Dasar Listrik dan Elektronika - Abdul Hamid; Hansi Effendi (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
This research aims to investigate the differences in student learning outcomes by applying the flipped classroom and conventional model. This study uses quasi-experiments with state group comparison design which was conducted in grade 10 of Electrical Installation Engineering. The simple random sampling techniques are used to determine the experiment and control class. The data were collected using student performance assessment instruments which were assessed from several aspects such as preparation, process, outcomes, safety, and reporting. There are differences in learning outcomes from grade 10 of Electrical Installation Engineering that applied the flipped classroom learning model and conventional model on the subjects of Basic Electrical and Electronics at Sekolah Menengah Kejuruan (SMK) Muhammadiyah 1 Padang. The learning outcome of the experimental class higher than the conventional ones. According to statistics, the differences are significant. The uses of flipped classrooms can be applied as an alternative in learning of Basic Electrical and Electronics Subject.